Students’ Perception on the Using of Google Translate in Translation Class at the 4th Semester of English Departemet of UIN Sjech M. Djamil Djambek Bukittinggi - Febyola, Febyola; Eliza, Eliza; Reflinda, Reflinda; Roza, Veni (Lembaga Yasin AlSys, 2023)
The using of Google Translate in translation class has been an issue whether it has to be avoided or not. The problem of this research was different perceptions among English students about the using of Google Translate in translation class. The purpose of this research was to find out students’ perception on the using of Google Translate in translation class based on cognitive, affective, and connative aspect. This research used a quantitative approach witha survey design. The population of this study were the students who had taken translation class at the fourth semester of English Departement in academic year 2021/2022 consisting of 37 students from 4 classes. The researcher used total sampling because the population are less than 100 students. Instrument of this research was questionnaire which consisted of 30 items. The researcher did the validity instrument through three experts. In analyzing the data, the researcher used quantitative descriptive analysis. Total percentage of data analysis was 67.07% for cognitive aspect, 69.77% for affective aspect, 57.99% for connative aspect. The average of three percentage was 64.94%. This percentage was good criteria. It means that the perception of the students was good. Thus, the result of the research showed that students who had taken translationclass dominantly agree the use of Google Translate in translation class.